Multifunctional Beverage Preparation and Dispensing System iDrink Station - Ahmad Ghassan Atallah; Khaled Mohammad Saadeh (My University, 2025)
This project aims to provide a practical and sustainable solution in the world of vending beverages by designing and building a machine that prepares cold and hot drinks using simple electronic and mechanical components. It focuses on facilitating and accelerating the automatic beverage preparation process, providing a smooth and fast user experience, making it ideal for offices, cafes, educational centers, public spaces, and even kiosks and small businesses. The machine operates using an Arduino controller, which precisely manages its various components, regulating the operation of sensors and controlling the movement of pumps and motors. It also includes an ESP module to enable communication with a mobile application. The beverage type is selected either manually via an electronic keypad or electronically through the app, offering flexibility in control. Additionally, the system can be activated using an RFID card or directly from the mobile application. Operating data, such as the beverage type (cold or hot), the selected flavor, temperature, and the number of cups prepared, is displayed on an LCD screen, providing the user with a comprehensive and clear experience. The mechanism involves pumping water from the tank, heating it as needed, selecting the appropriate beverage type, then pumping the desired concentrate or powder and mixing it into the cup, serving it to the user within a few minutes. These sequential steps allow the user to prepare a variety of drinks, such as mojitos, Vimto, iced tea, fruit juices, Zahra juice, coffee, Nescafe, or tea, with just the push of a button. This project represents a practical model for the concept of digital transformation in quick-service restaurants, combining simplicity in design with performance efficiency. The machine not only saves time and effort for users and workers, but also opens the way for the development of innovative small businesses in the beverage sector, especially with the approach of summer and the increased demand for cold and ready-to-drink beverages.